Giant pericardial tube roll aneurysm after the treatment of aortic interruption - Ulukan, Mustafa Özer; Yıldız, Yahya; Ata, Emin Can; Öztaş, Didem Melis; Erkanlı, Korhan; U?urlucan, Murat; Türko?lu, Halil (Thieme Medical Publishers, Inc., 2020)
Various techniques have been described for the treatment of interrupted aortic arch pathology. Graft interposition, either autologous or synthetic, is included among these methods. In this article, we present the images of giant pericardial roll aneurysm that was used for the treatment of aortic interruption during the newborn period.
Keywords: Interrupted Aortic Arch; Congenital Cardiac Surgery; Pericardial Roll